Data Build-up for the Construction of Korean Specific Greenhouse Gas Emission Inventory in Livestock Categories - S. G. Won (Asian-Australasian Journal of Animal Sciences, 2014)
Many studies on methane (CH4) and nitrous oxide (N2O) emissions from livestock industries have revealed that livestock production directly contributes to greenhouse gas (GHG) emissions through enteric fermentation and manure management, which causes negative impacts on animal environment sustainability. In the present study, three essential values for GHG emission were measured; i.e., i) maximum CH4 producing capacity at mesophilic temperature (37°C) from anaerobically stored manure in livestock category (B0,KM, Korean livestock manure for B0), ii) EF3(s) value representing an emission factor for direct N2O emissions from manure management system S in the country, kg N2O-N kg N−1, at mesophilic (37°C) and thermophilic (55°C) temperatures, and iii) Nex(T) emissions showing annual N excretion for livestock category T, kg N animal−1 yr−1, from different livestock manure. Static incubation with and without aeration was performed to obtain the N2O and CH4 emissions from each sample, respectively. Chemical compositions of pre- and post-incubated manure were analyzed. Contents of total solids (% TS) and volatile solid (% VS), and the ratio of carbon to nitrogen (C/N) decrease significantly in all the samples by C-containing biogas generation, whereas moisture content (%) and pH increased after incubation. A big difference of total nitrogen content was not observed in pre- and post-incubation during CH4 and N2O emissions. CH4 emissions (g CH4 kg VS−1) from all the three manures (sows, layers and Korean cattle) were different and high C/N ratio resulted in high CH4 emission. Similarly, N2O emission was found to be affected by % VS, pH, and temperature. The B0,KM values for sows, layers, and Korean cattle obtained at 37°C are 0.0579, 0.0006, and 0.0828 m3 CH4 kg VS−1, respectively, which are much less than the default values in IPCC guideline (GL) except the value from Korean cattle. For sows and Korean cattle, Nex(T) values of 7.67 and 28.19 kg N yr−1, respectively, are 2.5 fold less than those values in IPCC GL as well. However, Nex(T) value of layers 0.63 kg N yr−1 is very similar to the default value of 0.6 kg N yr−1 in IPCC GLs for National greenhouse gas inventories for countries such as South Korea/Asia. The EF3(s) value obtained at 37°C and 55°C were found to be far less than the default value.